The influence of the textural properties of activated carbons on acetaminophen adsorption at different temperatures - Galhetas, M. (2015)
The influence of temperature (20–40 °C) on the acetaminophen adsorption onto activated carbons with different textures was studied. Different temperature dependences, not explained by kinetic effects, were observed for carbons with different micropore size distribution patterns: adsorption capacity increased for pine gasification residues (Pi-fa) derived carbons and decreased for sisal based materials. No significant variation was seen for carbon CP. The species identified by 1H NMR spectroscopy on the back-extraction solution proved that during the adsorption process exist the conditions required to promote the formation of acetaminophen oligomers which have constrained access to the narrow microporosity. The rotation energy of the dihedral angle between monomers (estimated by electronic DFT methods) showed that conformations in the planar form are less stable than the non-planar conformation (energy barrier of 70 and 23 kJ mol-1), but have critical dimensions similar to the monomer and can access most of the micropore volume. The enthalpy change of the overall process showed that the energy gain of the system (endothermic) for Pi-fa samples (˜40 kJ mol-1) was enough to allow a change in the dimer, or even a larger oligomer, conformation to the planar form. This will permit adsorption in the narrow micropores, thus explaining the uptake increase with temperature. Non-continuous micropore size distributions centered at pore widths close to the critical dimensions of the planar form seem to be crucial for a positive evolution of the adsorption capacity with temperature.